PANGEMBANGAN WEBSITE UNIVERSITAS NEGERI PADANG MENGGUNAKAN METODE MODEL WATERFAL DAN FRAMEWORK CODEIGNITER - Syaflan Sandi Harta Putra; M. Giatman M. Giatman; Mukhlidi Muskhir; Hansi Effendi (Ensiklopedia of Journal, 2021)
Currently, the disclosure of data and information is something that must be accommodated in an agency, especially the Padang State University, one of which is the use of a website. The website has a very important role in conveying important information such as news, agendas, profiles, services and other academic services. Based on these needs, it is necessary to develop a website with an interactive design and have an easy interface system. In the old version of the website, it was created using the Drupal Content Management System (CMS), while the latest version was developed directly by UPT. PTIK Padang State University using the Codeigniter Framework and Bootstrap. The method in developing this website uses the Waterfall Model, this model is a model that is widely used for application development so it is very suitable to be applied to the development of the Padang State University website. The results of website development provide a significant change in visitor traffic every day with an average of 750 visitors per day.